Relations between Laboratorio di Sintesi Finale course of Politecnico di Milano and fashion design teaching in Brazil (ModaPalavra e-periódico, 2020)
From the experience in the Politecnico di Milano, followingLaboratorio di Sintesi Finale course, under the responsibilityof Professor Giovanni Conti, it was possible to record thesteps that configure aprocess of fashion design and acertain order for them to occur. During this period, it waspossible to observe how often vocabulary and practices ofindustrial design are used, which are sometimes relaxedaccording to the specific needs of fashion design.In additionto attending Conti's classes, an exploratory interview wasconducted with the Professor, aiming at collecting moreprecise primary data that were later treated respecting OralHistory methods for the construction of reports such asthose of Alberti (2013), Poupart (2008) and Velho (1980).Thus, the problematization produced as a result of thisresearch provided some reflections that expose theimportance of the practice of fashion design and itsinstitutionalization for the advancement of the field in Brazil.
Keywords: design steps; process; fashion design